2011
DOI: 10.1007/s13592-011-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry evidence about sperm competition in honey bee (Apis mellifera)

Abstract: -We tested whether flow cytometry can be used for assessment of viability of honey bee (Apis mellifera) sperm. The method was used to detect possible competition between the sperm of different drones. The flow cytometry analysis of semen stained with SYBR-14/propidium iodide revealed significant differences between fresh and freeze-thawed samples. The identification of populations corresponding to viable and nonviable sperm allowed us to assess the sperm viability. The comparison of single-drone semen with mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
(31 reference statements)
4
16
0
Order By: Relevance
“…Similar to another honeybee sperm FCM study , this investigation also identified additional populations of sperm in the data that appeared when freeze–thawing was used to kill cells. Initial experiments using an analog instrument (FACSCalibur, BD Biosciences) also used by Tofilski et al produced multiple populations, but without clear separation between live and dead cells. This study has found that use of digital flow cytometer allowed distinction of both peak area and peak height, important in the analysis of bee sperm because of their unusual shape.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar to another honeybee sperm FCM study , this investigation also identified additional populations of sperm in the data that appeared when freeze–thawing was used to kill cells. Initial experiments using an analog instrument (FACSCalibur, BD Biosciences) also used by Tofilski et al produced multiple populations, but without clear separation between live and dead cells. This study has found that use of digital flow cytometer allowed distinction of both peak area and peak height, important in the analysis of bee sperm because of their unusual shape.…”
Section: Discussionmentioning
confidence: 63%
“…We show that FCM, compared with fluorescence microscopy, is a faster and more accurate method to assess sperm viability in sperm samples of honeybees. Furthermore, we are able to resolve some of the technical issues reported in earlier published literature about the possible use of FCM for honeybee sperm . We show that killing sperm by freeze–thawing with liquid nitrogen (LN), which has previously been used to generate reference semen samples with known sperm viabilities, creates a distinct population with high PI fluorescence, likely due to membrane disruption and/or changes to chromatin structure which affect PI binding.…”
mentioning
confidence: 86%
“…Sperm motility reflects both energetic efficacy and the quality of the motility apparatus; it is also important for sperm transfer to a queen's spermatheca (Ruttner and Koeniger 1971;Baer 2005). Viability staining reflects functional quality of membrane permeability and was found to be especially useful for the evaluation of sperm competition in insects, including honeybees (Hunter and Birkhead 2002;Tofilski et al 2012). Measurements of mitochondrial membrane potential (MMP) is important for evaluating the function of mitochondria, which are particularly vital for the production of energy during sperm movement.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation of seminal fluids is related to sperm competition (Dixson & Anderson, 2002) and proteins contained in particular semen coagulate when in contact with the spermatozoa of another drone in order to immobilize them (Tofilski et al 2012). Although the drones in our study originated from one paternal colony, the chromosome complement transferred by the mother may have been different.…”
Section: Discussionmentioning
confidence: 91%